Fusion. (Makati City, Philippines : Foundation for Upgrading the Standard of Education, Inc., 2002)
This edition includes articles delivered at the monthly general assembly of the Foundation for upgrading the Standard of Education (FUSE) for the years, 2001 and 2002. Many speakers came with their outline and their delivery was generally spontaneous.
Section 1. Some trends and issues in Philippine education -- Section 2. Mass media, education and technology -- Section 3. Curricular reforms -- Section 4. Views from the field on the new basic education curriculum -- Section 5. Learning from the lessons of history -- Section 6. Alternative approaches and programs in Philippine Education -- Section 7. Initiatives for renewal/development -- Section 8. On scholarship.
Keywords: EDUCATION